Substitusi Tepung Ikan dengan Tepung Limbah Ikan Hiu (Carcharhinus sp.) terhadap Pertumbuhan, Efisiensi Pakan dan Survival Rate Ikan Lele Dumbo (Clarias sp.) [Subtitution of Fish Mill with Shark Waste Mill (Carcharhinus sp.) on Growth, Feed Efficiency and Fish Survival Rate of African Catfish (Clarias sp.) ] - Yudi Cahyoko; Muhammad Arief; Novan Agil Permana (Faculty of Fisheries and Marine Universitas Airlangga, 2015)
Abstract Currently, African catfish is developing quite rapidly, because African catfish is one of the important commodities in the fishery. Efforts to increase the production of African catfish is to improve the quality of feed. The purpose of this study was to determine the effect of the use of shark waste mill on the growth rate, feed efficiency and survival rate of African catfish fishing. The research method was experimental with completely randomized design (CRD). The research consisted of five treatments and four replications. The treatments used were: (A) shark waste mill at 0% and fish mill by 50%, (B) 5% shark waste mill and 45% fish mill, (C) 10% waste shark mill and 40% fish mill, (D) 15% waste shark mill and fish mill and 35% (E) 20% shark waste mill and 30% fish mill. The main parameters measured were growth, feed efficiency and survival rate. Supporting parameters measured were water quality. Analysis of the data using analysis of variance (ANOVA) and to determine the differences between treatments tested by Duncan Multiple Range Test. The results showed that the giving of shark waste mil on ration had highly different effects on growth rate and feed eficiency of african catfish. The feeding of waste shark mill in ration had no significantly different effect on Survival Rate (SR). The best dose of shark waste mill is treatment C (10%) with growth rate (1,26%/day), feed eficiency (38,64%) and survival rate (55%).